Physical, thermal and mechanical properties of areca fibre reinforced polymer composites — an overview - Loganathan, Tamil Moli; Hameed Sultan, Mohamed Thariq; Jawaid, Mohammad; Md Shah, Ain Umaira; Ahsan, Qumrul; Mariapan, Manohar; Abdul Majid, Mohd Shukry (Speinger, 2020)
Areca catechu, is a species of palm belonging to the family of Arecaceae/Palmae, grows vertically, to the height of 10 m to 20 m, the stem is straight, solitary and slender, 10 cm to 15 cm in diameter, with marks of annulated scars of fallen leaf sheaths. Areca fibres are predominantly extracted not only from the fruit as areca husk, but also from leaf stalks and fronds. In this review paper, areca fibre is compared with those of other representative species of the Arecaceae/Palmae family, such as the coconut tree and the palm tree, in terms of physical and mechanical properties. This review article also discusses the physical, mechanical and thermal properties of areca fibre and its composites. The review of known published data reveals that, while areca fibre has the potential to be used as an alternative reinforcement in polymer composites. Besides, it has been also noticed that some other species from the family of Arecaceae/Palmae have not been explored as natural fibre reinforcement in polymer composites either, thus revealing further options of natural alternative reinforcement to be investigated with regard to their potential to be used in fibre based composites for the automotive, aerospace, and construction industries.